2019
DOI: 10.1049/el.2019.2095
|View full text |Cite
|
Sign up to set email alerts
|

Game‐theoretic power allocation algorithm for downlink NOMA cellular system

Abstract: A new power allocation algorithm is proposed based on the Glicksberg game for cellular downlink non-orthogonal multiple access (NOMA) networks. First, a price-based user's utility function is proposed, and shown that it is effective and restrictive. Secondly, the Hessian matrix is used to derive an expression for power price based on the restricted transmission power and number of the served users in the cell. Then, the existence of a unique Nash equilibrium is proven and the optimum solution that maximises th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…where hm is the BS-UEm channel gain, eh is the channel estimation error, nm is a standard complex normal random variable ~CN(0,σ 2 ) which represents the additive white Gaussian noise (AWGN) at UEm with zero mean and variance σ 2 , and x(t) represents the transmitted signal which is given as [8] ), ( )…”
Section: System Model and Pa Algorithm System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…where hm is the BS-UEm channel gain, eh is the channel estimation error, nm is a standard complex normal random variable ~CN(0,σ 2 ) which represents the additive white Gaussian noise (AWGN) at UEm with zero mean and variance σ 2 , and x(t) represents the transmitted signal which is given as [8] ), ( )…”
Section: System Model and Pa Algorithm System Modelmentioning
confidence: 99%
“…Power allocation (PA) is considered an essential method to raise the data-rate and the energy efficiency in the NOMA system, where various powers are assigned to the cell's users and combined on the same subcarrier at the same time [7]. A game-theoretic power allocation mechanism is studied in [8] where power is assigned to the users to maximize the total throughput and the average throughput in the downlink NOMA cellular system. However, the investigation of the system performance based on the proposed algorithm in [8] is under the assumption that the BS has perfect channel state information (CSI) which is difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aldebes et al aimed at maximizing the sum rate in the downlink NOMA cellular system. Glicksberg game-based algorithm is used to allocate the power between different numbers of users [ 15 ]. Omslandseter et al considered the problem of power allocation as a variation of the Knapsack Problem, and solved it through a greedy solution [ 16 ].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, a game-theoretic approach is studied in [26] where NOMA is applied to ALOHA for deciding the transmission probability. Based on the Glicksberg game, Aldebes et al proposed a power allocation algorithm for cellular downlink NOMA networks [27]. In particular, for the power allocation algorithm, the authors proposed a price-based user's utility function, which is shown to be restrictive if the allocated power beyond a threshold value causes a decrease in the utility value.…”
Section: Related Workmentioning
confidence: 99%